Konsep Al-Sunnah menurut ahli hadith - Aminudin Basir @ Ahmad; Mohd Radzi Othman; Nik Yusri Musa (Universiti Kebangsaan Malaysia, 2006)
Al-Sunnah has been discussed from perspective of al-Fiqh, Usul al-Fiqh andUsul al-Hadith. The meaning of al-Sunnah from Ahl al-Hadith point of view iswider and deeper. Ahl Hadith have a good knowledge and understanding fortheir interaction with al-Sunnah throughout their lives. To Ahl al-Hadith, al-Sunnah includes many elements such as aqidah, fiqh and akhlak. This paper will be focussing on the meaning of al-Sunnah from Ahl al-Hadith point of view